A STATE SMALLER THAN ITS TERRITORY: STRUGGLES OVER IDENTITY AND LOYALTY ON THE SOUTHEASTERN BORDERLAND OF LITHUANIA - Norkūnaitė, Marija (Politologija, 2016)
Due to the ethnic composition of the population, one-party rule by the Electoral Action of Poles in Lithuania (further – LLRA) and a tense relationship with the central government, the Southeastern borderland of Lithuania is often referred to as the “Fortress” of Lithuanian Poles. However, a deeper look into the context reveals that the problem is far more complicated than the matter of ethnicity. Rather, it raises questions about people’s loyalty to the state and their identification with it. On that account, the aim of this study is to find out what actors are engaged in the struggles over power on the Southeastern borderland of Lithuania and what mechanisms are being used to hinder the state from spreading a uniform national identity on its border regions. In order to answer these questions, a field study in Salcininkai has been conducted. The analysis is based on the State-in-Society theory, presented by J. S. Migdal. The first part of the analysis is focused on the presence of other (non)political actors in the region. The conclusion made is that the political entrenchment by one party has resulted not only from the measures used by the ruling party, but was also caused by the lack of consistency and continuity in the policies towards the region by other major political players in Lithuania. Furthermore, the majority of the organisations operating in the area (state agencies, business, non-governmental organisations) are subjugated to the control of the ruling party and should not be considered as independent actors. In the second part of the analysis, the measures used by LLRA are divided into two categories: (1) administrative-material capacities; (2) symbolic resources. The first category covers such measures as threats to take away jobs, pensions, allowances as well as information control. By exploiting the frustration of the people and the exclusion of the region from the rest of the country as well as the feelings of nationality and soviet nostalgia, the party has become able to construct the narrative of “one‘s people” that allows it to take the place of the state in the minds of the people. As a result, Lithuania has become smaller than its territory. The results suggest that the State-in-Society theory, based on the practices found in the Third world countries, allows to explain processes happening on the Southeastern borderland of Lithuania and reveals a more complex picture of the situation than it is assumed nationally. An application of this theory to a case study in a country with a completely different political and historical context not only allows to look at the problems it faces in a new light, but also extends the geographical scope of the theory and allows to see new aspects of it.